Clinical Medical Training during the First Wave of COVID-19 Pandemic: Universiti Tunku Abdul Rahman, Malaysia Experience - Bee Sun Lee; Naing Soe Yan; Xin Jet Din; Teck Han Ng; Soon Keng Cheong (UiTM Press, 2022)
Introduction: Clinical training forms the fundamental element in medical training in all medical schools. Unfortunately, most traditional face-to-face clinical teaching activities had to come to a halt during the COVID-19 pandemic and be replaced with online teaching learning (OTL) sessions. This paper aims to share our experience of implementing OTL sessions for our UTAR medical clinical years students during the first wave of COVID-19 pandemic and assess its outcome by collecting students' feedback. Methods: This was a cross-sectional questionnaire-based study conducted among MBBS clinical year students of Faculty of Medicine and Health Sciences, UTAR. The questionnaires survey feedback on OTL sessions, examinations conducted, and replacement classes. Results: A total of 113 medical students participated in the survey. The third to fifth year students' response rate were 93.0%, 59.2% and 100.0% respectively. More than 50% of the students scored 3 (good) for the components asked. It was found that 17.2% of fourth year students and 11.4% of fifth year students were in the opinion that replacement classes were not necessary and scored it 1 (poor). On the conduct of clinical exam, 17.5% of third year students, 37.9% of fourth year students and 25.0% of fifth year students graded it 4 (excellent). More than 60% of students preferred the traditional physical classes. Conclusions: The modifications of teaching done in this academic year 2020/2021 and the feedbacks gathered from the students will serve as a reflection to the faculty for future planning.